Analysis of power losses in multilevel pulse-width modulation inverters - Manat, Symbat; Yugay, Vyacheslav; Kaliaskarov, Nurbol (Eastern-European Journal of Enterprise Technologies, 2022)
The paper describes the types of multilevel pulse-width modulation, as well as methods for obtaining control signals for the inverter power switches for each of the types. The dependence of the harmonic composition of the output voltage of the inverter on the number of levels and the switching frequency of the keys of each level is analyzed. By modeling, the dependences of the transistor junction temperature on the number of voltage levels, switching frequency and load power are determined. The power switching system of an inverter with phase-shifted pulse-width modulation in high-frequency mode is analyzed, the dependence of switching losses on inductance is investigated. The ways of solving or improving the control systems of the conductivity losses of the converter flowing through the primary winding of a high-frequency transformer during the free-running period are formulated. The importance of this direction for the technological development of the economy, where efficiency improvements can lower individual utility bills, create jobs, and help stabilize electricity prices and volatility is shown. The most important stage of inverter design is called structural synthesis stage – the choice of topology and modulation algorithm that will ensure the greatest efficiency of the device. In addition, since the efficiency and reliability of inverters depend on the efficiency and reliability of secondary electricity consumers, the task of optimizing inverter circuits is a cornerstone for the effective development of technology and economy. The maximum dynamic power loss at a PWM frequency of 1 kHz reaches only 80 watts compared to the static power loss value of 800 watts